Identification and functional analysis of two novel mutations in the CBS gene in Polish patients with homocystinuria - Orendáè, Marek; Pronicka, Ewa; Kubalska, Jolanta; Janosik, Miroslav; Sokolová, Jitka; Linnebank, Michael; Koch, Hans Georg; Kozich, Viktor (Human mutation, 2004)
Homocystinuria due to cystathionine beta-synthase (CBS) deficiency is an inherited disorder of homocysteine transsulfuration, which manifests by neurological, vascular and connective tissue involvement. So far, 130 pathogenic mutations have been recognized in the CBS gene. We examined 10 independent alleles in Polish patients suffering from CBS deficiency, and we detected four already described mutations (c.1224-2A>C, c.684C>A, c.833T>C, and c.442G>A) and two novel mutations (c.429C>G and c.1039+1G>T). The pathogenicity of the novel mutations was demonstrated by expression in E.coli. This is the first published communication on mutations leading to CBS deficiency in Poland.
Keywords: mutace; cystathionin-beta-synthasa; Humans; Homocystinuria; lidé; Poland; Mutation; DNA Mutational Analysis; Cystathionine beta-Synthase; homocystinurie; mutační analýza DNA; Polsko